2016
DOI: 10.5694/mja16.00104
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, clinical impacts and current clinical management of Helicobacter pylori infection

Abstract: Helicobacter pylori infection is a major cause of morbidity and mortality worldwide. More than 50% of the global population is estimated to be infected. Differences in prevalence exist within and between countries, with higher prevalence seen among people with lower socio-economic status. Most transmission of infection occurs early in life, predominantly from person to person in the family setting. H. pylori is the cause of most peptic ulcer disease, gastric cancer and gastric mucosa-associated lymphoid tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
76
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 42 publications
(114 reference statements)
2
76
1
4
Order By: Relevance
“…In children, the incidence of H. pylori infection was quite low, but will increase up to 20% in the age of 40 and 50% in the age of 60. 15 The result of this study was similar to the study performed by Darya in 2009 which found that the prevalence of H. pylori infection in gastritis patients in Sanglah Hospital was 18.8% using immunochromatography method. 16 Target population in both studies was similar, which was dyspepsia patients who visited each hospitals for treatment.…”
Section: Discussionsupporting
confidence: 79%
“…In children, the incidence of H. pylori infection was quite low, but will increase up to 20% in the age of 40 and 50% in the age of 60. 15 The result of this study was similar to the study performed by Darya in 2009 which found that the prevalence of H. pylori infection in gastritis patients in Sanglah Hospital was 18.8% using immunochromatography method. 16 Target population in both studies was similar, which was dyspepsia patients who visited each hospitals for treatment.…”
Section: Discussionsupporting
confidence: 79%
“…Taken together, the IL‐23/Th17 axis which comprise the major immunopathogenesis of psoriasis may also act as an inflammatory pathway in gastric carcinogenesis via H. pylori infection . Although H. pylori infection has been falling due to better living conditions and sanitation, the prevalence is still higher in Korean population compared to the western countries . Along with the shared immunopathogenesis of psoriasis and H. pylori ‐induced gastric cancer, this epidemiological difference might contribute to an increased risk of gastric cancer in psoriatic patients in our cohort, but not in previous Western studies.…”
Section: Discussionmentioning
confidence: 54%
“…Moreover, antral biopsies were assessed for Helicobacter‐like organisms and duodenal biopsies for visible pathogens. Additional testing of H. pylori was not considered necessary in the absence of suggestive microscopic changes (such as histological gastritis) and H. pylori in Australian children is now rare . The similar racial distribution in cases and controls also minimises the potential influence of diet and/or enteric infections on duodenal eosinophil counts.…”
Section: Discussionmentioning
confidence: 99%